An exquisitely preserved tiny bark‐gnawing beetle (Coleoptera: Trogossitidae) from mid‐Cretaceous Burmese amber and the phylogeny of Trogossitidae. (11th August 2021) - Li, Yan‐Da; Tihelka, Erik; Leschen, Richard A. B.; Yu, Yali; Ślipiński, Adam; Pang, Hong; Huang, Diying; Kolibáč, Jiří; Cai, Chenyang
Abstract: The first fossil representative of the cleroid family Trogossitidae is described from mid‐Cretaceous Burmese amber. Microtrogossita qizhihaoi Li & Cai gen. et sp. nov. is unique among Trogossitidae in the relatively widely separated procoxal and mesocoxal cavities, weakly asymmetrical antennal clubs, coarsely facetted eyes, coarse sculpture of dorsal and ventral surfaces of thorax in comparison with tiny body size, and the absence of spines along side margin of tibiae. Morphological characters of the fossil were analyzed together with representatives of 44 extant genera of Cleroidea (Peltidae, Lophocateridae, and Trogossitidae) in a matrix of 93 characters. Microtrogossita qizhihaoi was resolved as a member of Trogossitini within Trogossitidae. The tribal composition of Trogossitidae is discussed in light of our re‐analysis of a previously published four‐gene dataset under a site‐heterogeneous model. The recently described lophocaterid Mesolophocateres pengweii Yu, Leschen & Ślipiński syn. nov. from Burmese amber is suggested to be a junior synonym of Burmacateres longicoxa Kolibáč & Peris. Abstract : The first fossil representative of the cleroid family Trogossitidae is described from mid‐Cretaceous Burmese amber. Microtrogossita qizhihaoi Li & Cai gen. et sp. nov. has a unique character combination among Trogossitidae. The fossil was resolved as a member of Trogossitini within Trogossitidae based on a morphological phylogenetic analysis. The tribal composition of Trogossitidae is discussed in light of our re‐analysis of a previously published four‐gene dataset under a site‐heterogeneous model.